The conservation of cultural landscapes - Agnoletti, Mauro (CABI, 2006)
The conservation and management of cultural landscapes, interpreted as the result of the interrelationships among economic, social and environmental factors through time and space, emerges as essential components in the definition and application of a modern approach to sustainable development.